2018
DOI: 10.1002/vjch.201800087
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of reduced graphene oxide for high‐performance supercapacitor

Abstract: Reduced graphene oxide (rGO) were prepared by thermal reduction technique from graphene oxide (GO) in N 2 gas atmosphere at 600 o C for 1 h. The results shown that rGO possessed a multiple layer structure and a specific surface area BET of 389.9 m 2 /g. The electrochemical properties of the rGO materials have been investigated for supercapacitors. Electrochemical measurements show that rGO exhibit a specific capacitance of 85.3 F/g at 1 A/g, and still kept 85 % capacitance after 1000 cycles at 1 A/g, indicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 24 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…The last allotropic form of carbon graphene has demonstrated that it possesses remarkable physicochemical properties (specific surface area between 1500–2600 m 2 g −1 ) [ 21 , 22 ] that can be exploited for many electrochemical applications. Graphene possesses a single layer as a carbon sheet with the thickness of an atom.…”
Section: Methods Of Synthesis Nps@go Nanocompositesmentioning
confidence: 99%
“…The last allotropic form of carbon graphene has demonstrated that it possesses remarkable physicochemical properties (specific surface area between 1500–2600 m 2 g −1 ) [ 21 , 22 ] that can be exploited for many electrochemical applications. Graphene possesses a single layer as a carbon sheet with the thickness of an atom.…”
Section: Methods Of Synthesis Nps@go Nanocompositesmentioning
confidence: 99%
“…10b) in saturated argon exhibited a large non-faradaic current, indicating a substantial increase in the electrochemical surface area and electrical conductivity with the application of rGO on the WE. 53 In the saturated O 2 electrolyte, a peak is present in both the cathodic and anodic scans. The cathodic peak current density can be attributed to the ORR.…”
Section: Resultsmentioning
confidence: 99%
“…We chose to synthesize CoNi/rGO to take advantage of the electron conductive rGO sheets, their capability of dispersing the nonconductive CoNi oxide, and the synergetic effect of forming binary CoNi oxides. 19,36 In our work, the molar ratio of Co : Ni and CoNi loading amount on GO were varied. The formed catalysts were examined for their morphological and crystal structures, electrochemical catalytic properties in ORR and OER, and ZAB discharge-charge cycle performance at the air cathode.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to synthesize CoNi/rGO to take advantage of the electron conductive rGO sheets, their capability of dispersing the nonconductive CoNi oxide, and the synergetic effect of forming binary CoNi oxides. 19,36…”
Section: Introductionmentioning
confidence: 99%